Potencial evocado auditivo de tronco encefálico em equinos - Gama, Juliana Almeida Nogueira da [UNESP] (2014)
Hearing is one of the main points of the communication process with the environment both humans and animals. The Auditory brainstem response (BAEP Brainstem Auditory-Evoked Potential) is a method that has been used in humans, dogs, cats, cattle and horses in order to identify possible hearing impairment that can’t be diagnosed during physical examination . The BAEP evaluates the integrity of the auditory pathway from the cochlea to the brainstem and allows the identification of animals with sensorineural and conductive deafness. Despite the importance of BAEP, no study to standardize its use in horses in Brazil was found. Thus, the objective of this study was to standardize the methodology for obtaining records to verify the wave latencies obtained in the examination for this species. 21 adult horses, males and females were used without previous history of hearing disorders. To perform the test, the animals were sedated with detomidine hydrochloride. Latencies of waves I, II, III, IV and V, as well as the intervals I-III, III-V and IV were identified. The mean latencies of the waves were, I wave 2.4 ms; wave II 2.74 ms ; wave III 3.61 ms; wave IV 4.61 ms and wave V 5.49 ms. The mean latencies of interpeaks were I-III 1.37; III-V 1.88 and I-V 3.26. The description of the methodology used and the availability of records and latencies can serve as a reference for studies in this species